Fetoscopic Laser Therapy for Twin–Twin Transfusion Syndrome: Beyond Current Gestational Age Limits - Baud, David; Windrim, Rory; Keunen, Johannes; Ryan, Greg (American Journal of Perinatology, 2014)
Both “early” (< 16 weeks' gestation) and “late” (> 26 weeks' gestation) presentations of twin–twin transfusion syndrome (TTTS) are rare and challenging complications of monochorionic/diamniotic twin pregnancies. Growing evidence suggests that fetoscopic laser therapy for both “early” and “late” TTTS is feasible, safe, and yields similar outcomes to cases treated between 16 and 26 weeks' gestation. We suggest reevaluation of conventional gestational age guidelines for laser therapy for TTTS.
Keywords: laser therapy; fetoscopy; monochorionic twins; neonatal mortality; twin–twin transfusion syndrome